Analysis of Stunting Incidents in Depok: Analisis Kejadian Stunting di Depok - Hanifah, Laily (Universitas Mohammad Husni Thamrin, 2025)
Indonesia still faces the problem of stunting with a prevalence of above 20%. To achieve the government's target of reducing the prevalence of stunting to 14%, a lot of effort is needed. This research was conducted aimed at analysing the incidence of stunting in Depok because the prevalence of stunting in Depok is still high. This study used qualitative research method by using in-depth interview to 5 informants. The results of this research found that the main causes of stunting are a lack of nutritious food intake and infectious diseases which are influenced by parenting patterns and family socio-economics. To overcome this, the Depok city government is trying to carry out early detection of pregnant women with chronic energy deficiency (CED), anaemia and providing additional food for pregnant women with CED. Academics routinely hold advocacy and provide policy and program recommendations from research conducted, so that it is based on studies conducted in Indonesia and the world. Keywords : Stunting, Toddlers, Depok